Hubris and Unethical Decision Making: The Tragedy of the Uncommon - McManus, Joseph (Journal of business ethics, 2018)
The research theorizes how hubris impacts ethical decision making and develops empirical evidence that earnings manipulation is more likely at firms led by CEOs influenced by hubris. The theory posits that hubris impairs moral awareness by causing decision makers to ignore external factors that otherwise drive such awareness. Additionally, these individuals apply a flawed subjective assessment of the decision they face which further impairs moral awareness. The predicted result is that hubris leads managers to invoke an amoral decision process which causes a higher incidence of unethical behavior among these individuals. An empirical study investigates the relationship between CEO hubris and the unethical practice of earnings manipulation. This study finds a significant correlation between CEO hubris and earnings manipulation at the firms they lead, an outcome broadly consistent with the theory developed.